Development Of Interactive Animation Media to Improve the Vocabulary of New Students in Arabic Language Matriculation - Eka Zahro'u Rosidah; Nunik Zuhriyah Z (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2026)
This study aims to develop interactive animation media as a means of learning vocabulary for new students in the Arabic language matriculation program at IAI Badrus Sholeh Kediri. The background of this study is based on the low mastery of basic vocabulary among new students, which has an impact on their difficulty in following advanced lectures. This study uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Data collection instruments include observation, interviews, expert validation questionnaires on material and media, and vocabulary mastery tests for students. The results of the study show that the interactive animation media developed is considered very suitable for use based on the assessments of subject matter experts and media experts, with an average validation score in the very good category. The implementation of this media in matriculation has proven to be effective in improving students' vocabulary mastery as demonstrated by the increase in test scores before and after using the media. In addition, students' responses to this interactive animated media were also very positive, as they felt more motivated and assisted in understanding new vocabulary an enjoyable manner.